Cooperative Banks and Financial Stability - Cihak, Martin (IMF Working Papers; Working Paper ;, 2007)
Cooperative banks are an important, and growing, part of many financial systems. This paper empirically analyzes the role of cooperative banks in financial stability. Contrary to some suggestions in the literature, we find that cooperative banks are more stable than commercial banks. This finding is due to the lower volatility of the cooperative banks' returns, which more than offsets their lower profitability and capitalization. This is most likely due to cooperative banks' ability to use customer surplus as a cushion in weaker periods. We also find that in systems with a high presence of cooperative banks, weak commercial banks are less stable than they would be otherwise. The overall impact of a higher cooperative presence on bank stability is positive on average but insignificant in some specifications.